Jonathas Serrano em 1932: um escolanovista católico em meio às polêmicas educacionais de seu tempo - Romero, Maria Helena Cicci (2020)
The main objective of this research is to understand the educational thinking of Jonathas Serrano, with special attention to the investigation of the approaches and distances from the ideals of Escola Nova expressed in the 1932 Manifesto, through the analysis of his work Escola Nova: a serene debate in one word passionate, published in 1932. To this end, I present the Catholic sociability networks in which Jonathas Serrano was inserted at the beginning of the 20th century. His trajectory and production are significant of an intellectual who participated in the process of building the writing of national history, as well as the training of Brazilian secondary school teachers, and will be analyzed in the light of theoretical contributions from the areas of the History of Intellectuals and History Cultural. The critical reading of Serrano's book, in which he justifies the reasons for not having signed the Manifesto of Pioneers of New Education of 1932, is the main objective of this thesis. In that book, the author presents himself as a favorable enunciator for the Church's political, educational and cultural project, directly polemicizing the self-titled “pioneers”. With regard to the History of Intellectuals, the bibliographic review referring to the author Jonathas Serrano is carried out based on Sirinelli's proposal (2003), which indicates three keys of analysis for the study of intellectuals: itineraries, networks of sociability and generation. As an instrument of analysis of the work, and aiming to understand the appropriations and representations of Jonathas Serrano, who was an intellectual of the group of Catholics who approached “the errors and exaggerations” of Escola Nova, this text uses the theoretical conceptions of appropriation and representation, conceived in the studies of Chartier (1990), as well as the concepts of dialogism and polyphony, from Bakhtinian thought (2011). That said, it was possible to realize that, despite being considered traditional and conservative by the intellectuals of that period, there was a fine line of thought in relation to the principles of the New School and the philosophy of Catholicism, as he tried to reconcile them. them with regard to education.